Pengaruh Pengetahuan Wajib Pajak, Tarif Pajak, Kesadaran Perpajakan, dan Sanksi Perpajakan Terhadap Kepatuhan Perpajakan pada Pelaku Usaha di Kabupaten Bekasi Periode 2011-2019 - Puspitasari, Intan; Hartelina, Hartelina; Suartini, Sri; Nunung Nurhasanah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze and explain how much influence taxpayer knowledge, tax rates, tax awareness and tax sanctions have on tax compliance among business actors in Bekasi district for the 2011-2019 period partially and simultaneously. The research method used in this research is a quantitative verification approach. The population used in this research is Business Taxpayers in Bekasi Regency. With a sample of 100 samples. The data analysis used is multiple linear regression analysis with partial and simultaneous hypothesis testing. The research results show that taxpayer knowledge has a positive and significant effect on taxpayer compliance. This shows that the higher the knowledge a taxpayer has, the higher the taxpayer's compliance in paying taxes. Taxpayer awareness has a positive and significant effect on taxpayer compliance. This means that the level of awareness regarding compliance in paying taxes is still low. Tax sanctions have no effect on taxpayer compliance. This explains that the existence of sanctions does not make taxpayers obedient in paying their taxes.